The fuzzy discrete-time robust regulation problem an LMI approach. - Castillo-Toledo, B. (IEEE Transactions on fuzzy systems)
This paper is concerned with the design of a robust regulator capable of achieving trajectory tracking for discrete-time nonlinear systems under parameter uncertainty. By assuming that the behavior of the nonlinear system is described, at least locally, by a Takagi-Sugeno dynamic fuzzy model, an approach based in the combination of this fuzzy modeling and the regulator theory is presented. Conditions for the existence of a robust regulator under this approach are then derived and extended to include the use of the linear matrix inequality (LMI) technique.